Numerical analysis of asphalt mixture and comparison with physical Marshall test - Rimša, Vytautas; Kačianauskas, Rimantas; Sivilevičius, Henrikas (Journal of Civil Engineering and Management, 2014)
This paper addresses simulation of asphalt on the macroscopic scale, using the Discrete Element Model (DEM). Asphalt mixture is considered as a particulate solid composed of relatively stiff deformable layered spherical particles embedded into a homogenised matrix. The discrete model presents a 3D network of one-dimensional elements connecting particle's centres and comprising mutual interaction of particles. The contribution of the film layer and the interface thickness for normal stiffness is described analytically and illustrated by simulation results. Development of the normal interaction model of layered particles contacting via interface on the meso scale is the key point of the current development. The model applied aiming to simulate deformation of asphalt mixture is able to capture properties of the weaker matrix interface while layered particle comprises of bitumen film in meso scale. The developed technique is applied for simulation of Marshall test, i.e. diametric compression of cylindrical specimen, widely used for characterisation of asphalt mixtures. Finally, suitability of the model is illustrated by comparison with the available experimental results.